Determinanten der Weiterbildungsbereitschaft: Ergebnisse eines faktoriellen Surveys unter Arbeitslosen - Christopher Osiander; Martin Dietz (Journal for Labour Market Research, 2016)
– Publically sponsored further trainings for the unemployed are an important measure of active labour market policies (ALMP) in Germany. Current discussions within this context also focus on the willingness to participate, which is an important prerequisite for the success of the programs. Financial incentives may foster both participation and successful completion, thereby reducing opportunity costs of these measures. We investigate the question what factors determine the motivation to participate by conducting a CATI survey among around 4000 unemployed persons from the unemployment insurance system (Social Code III) and the means-tested basic income support system for needy recipients (Social Code II). We use a factorial survey - also known as vignette analysis - in combination with administrative data of the Federal Employment Agency (FEA), the latter providing detailed information about the individual labour market history. Multivariate analyses suggest that a program's duration, monthly bonus payments in addition to regular unemployment benefits, future job prospects and gratifications for successful completion influence the probability of participation mostly in the theoretically expected way.
Keywords: 330; Arbeitslose; Weiterbildungsbereitschaft - Determinanten; Weiterbildungsförderung; arbeitsmarktpolitische Maßnahme; Ausbildungszeit; ökonomische Faktoren; Bildungsertrag; Arbeitsmarktchancen; Weiterbildungsbeteiligung; Arbeitslosengeld; Leistungshöhe